TEACHING READING RECOUNT TEXT BY USING THIEVES STRATEGY - Fitri Novia; Ratna Nery (Language and Education Journal, 2019)
The purpose of the study was to find out whether or not there was a significant difference in reading comprehension between the students who were taught by using THIEVES (Title, Heading, Introduction, Every first sentence, Visual, End of paragraph, Summary) strategy and that of those who were not.The quasi-experimental method was used to conduct the research. The population of the study was all of the eighth-grade students of SMPN 2 Teluk Gelam. In this study, the purposive sampling method was used.The total numbers of the samples were 62 students. The instrument of this research was 30 questions about recount text in the form of multiple-choice test. To analyze the data, t-test was used. Based on the result of independent sample t-test, the value of tobtained was 3.718 at significance level p<0.05 in two-tailed testing and df=60, the critical value of ttable was 2.0003. Since the value of tobtained (3.718) was higher than ttable (2.0003) and pvalue (0.000) was less than αvalue 0.05, it meant that there was a significant difference in reading comprehension between the students who were taught using THIEVES strategy and that of those who were not. Hence, THIEVES strategy could improve the eighth-grade students’ reading skill at SMP Negeri 2 Teluk Gelam.